Geospatial Approaches to Model Renewable Energy Requirements of the New Capital City of Indonesia - de Vries, Walter Timo; Schrey, Marc (Frontiers in Sustainable Cities, 2022)
Predicting how a planned city will develop and expand after its construction, and which resources, such as energy, the city will need over time is only possible if one can rely on similar examples and reliable models. Given the existing spatial plans for the design of the new capital city of Indonesia, there is a need to develop and compare city development scenarios – in spatial expansion, population size, resource, energy and food requirements. A combination of various geospatial data approaches can address this knowledge and assessment gap. This article investigates spatial expansion, forest encroachment and sustainable energy infrastructure requirements using open access geodata and models. The hypothesis is that the constitution of the new capital city of Indonesia can rely on existing energy infrastructures but may also need to rely on additional resources. The research approach was to collect and integrate different types of geospatial data related to land use, terrain characteristics and population growth assumptions and connect these to both urban growth models and predictions and energy. This relied on land use change methodologies and urban growth models to simulate and predict spatial effects, with ca particular focus on the expansion of energy requirements. The choice to focus on energy requirements additionally required a comparison of different kinds of energy sources, such as solar and wind energy. The conclusion is that all design and expansion scenarios indicate a possible spatial conflict between locating sustainable energy production facilities with maintaining ecologically sensitive areas. A possible solution is to make use of existing mining infrastructures to enhance sustainable energy production and to make use of dual land and water solar energy systems.